2003
DOI: 10.1039/b212276f
|View full text |Cite
|
Sign up to set email alerts
|

Some structural and electronic properties of MX3(M = Ln, Sc, Y, Ti+, Zr+, Hf+; X = H, Me, Hal, NH2) from DFT calculations

Abstract: The geometry of trivalent homoleptic d0 MX3 (X = H, Me, Hal, NH2) complexes for the entire lanthanide family, neutral group 3 and cationic group 4 metal center complexes have been studied with DFT(B3PW91) calculations. The geometrical parameters are in good agreement with the available experimental data. The degree of pyramidalization of the metal is discussed. The hydride and alkyl complexes are strongly pyramidal. In the case of the halide, a pyramidal structure is preferred for fluoride and the systems beco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
68
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 63 publications
(71 citation statements)
references
References 67 publications
3
68
0
Order By: Relevance
“…Theoretical calculations can indeed help in interpreting experimental findings by providing tools for a detailed description of the metal-ligand bond. [26][27][28][29][30][31][32][33][34][35][36][37][38] However, they should not be analyzed without a direct comparison with experiments whereas experimental data are rather scarce, especially for heavy trivalent actinides. To date, theoretical studies dedicated to trivalent rare earth complexes have thus been mainly applied to structural data, with very satisfying agreements, but other computational analyses, and notably energetic analyses, have seldom been validated.…”
Section: Introductionmentioning
confidence: 99%
“…Theoretical calculations can indeed help in interpreting experimental findings by providing tools for a detailed description of the metal-ligand bond. [26][27][28][29][30][31][32][33][34][35][36][37][38] However, they should not be analyzed without a direct comparison with experiments whereas experimental data are rather scarce, especially for heavy trivalent actinides. To date, theoretical studies dedicated to trivalent rare earth complexes have thus been mainly applied to structural data, with very satisfying agreements, but other computational analyses, and notably energetic analyses, have seldom been validated.…”
Section: Introductionmentioning
confidence: 99%
“…The traditional interpretation of the agostic interaction cannot be satisfactory. In a study of La{CH(SiMe 3 ) 2 } 3 and La{N(SiMe 3 ) 2 } 3 , we have suggested that the elongation of the β Si-C bond is due, in part, to a derealization of the lone pair used for Ln-R bonding for R = CH(SiMej) 2 and N(SiMe 3 ) 2 within the ligand (35,36). This interpretation is not new in the literature (48).…”
Section: The Ionic Character Of the Ln-x Bond And The Agostic Interacmentioning
confidence: 87%
“…The nature of the Ln-X bonding has been the subject of several papers (15-17, 36). The lanthanide elements are electropositive centers resulting in ionic Ln-X bonding.…”
Section: The Electronic Structure Of the Ln-x Bondmentioning
confidence: 99%
“…[16] Indeed, it implies at least one step with an activation barrier of approximately 45 kcal mol 2 + is facile at high dihydrogen pressures, suggesting direct hydrogenolysis of alkyl complexes. [7] In conclusion, the unexpected formation of a cationic zirconium a-tetrahydrofuranyl complex via a cationic silyl intermediate was suggested by kinetic studies and DFT calculations.…”
mentioning
confidence: 99%
“…Because reactions of alkyls with dihydrogen are known to proceed with relatively low activation barriers between 15 and 20 kcal mol À1 , the formation of 2 appears to be a complicated process. [16] Indeed, it implies at least one step with an activation barrier of approximately 45 kcal mol À1 (C À H bond activation of THF by the alkyl ligand). The formation of [{(Me 3 TACD)ZrA C H T U N G T R E N N U N G (m-H) 2 } 2 ] 2 + is facile at high dihydrogen pressures, suggesting direct hydrogenolysis of alkyl complexes.…”
mentioning
confidence: 99%